Diagnóstico de la participación de la mujer lojana en las empresas de comercialización de productos de primera necesidad (autoservicios y supermercados) de la ciudad de Loja - Pogo Pineda, Maritza del Rocío (2016)
At the moment at world level the economic situation and the diverse social, cultural processes, politicians affect at all the levels and also to great part of the companies that cross the constant challenges of the competition and the technology in that some are affected mostly; for that that, it is they indispensable the diagnoses to more in those that the woman participates that you/he/she takes to the attainment of her objectives and in you/he/she offers of to be and to have a better and bigger participation in a market that every time is more competitive. In our country the woman's participation in the conduction of the companies specifically in supermarkets and self-service of products of first necessity (Self-service and Supermarkets), achieving this way the generation of capital entrance. Traditionally this very venturesome activity is very characteristic of the developing countries. The activity of commercialization of products of first necessity is also carried out by big chains of supermarkets, like for Self-service. Loja still maintains an evident dependence of the external market as for the supply of products of first necessity and of technology; characterized by a great trade index and little level of productivity that he/she makes that our economy is weak and a managerial backwardness is generated. Considering their high inflationary level that limits to the improvement of the conditions of life additionally. Before this critical situation for the companies, the present proposed project, heads to the I diagnose of the woman's lojana participation in the companies of commercialization of products of first necessity, exposing as main objective to Carry out a Diagnosis of the woman's lojana participation in the companies of commercialization of products of first necessity (self-service and supermarkets) of the city of Loja, with the purpose of knowing the contribution that toasts to the managerial and social development. Likewise, for the attainment of this end he/she thought about the following fulfilled objectives: “To carry out a diagnosis of the activities that the woman carries out in the self-service and supermarkets of the city of Loja, using the tool FODA. “To know the type of managerial leadership that the manager applies in front of her employees. “Proposal: To determine the competitive level that you/they have the companies that the women administer, with the purpose of knowing the contribution that you/they toast to the managerial development of Loja The present project was carried out in the city of Loja, achieving you to detect in the companies, negative aspects as for example: permanent rotation and insufficient training and motivation to the personnel; and I eat positive aspects they stand out for example: the commercialization of products of first necessity. In the realization of the external analysis and I intern of the supermarkets and self-service, one carries out an analysis FODA, competitive advantages that allow to the manager in the taking of their decisions and inside the local market, to improve their quality of attention to the client obviating empiric knowledge for scientific. The different ones technical and methods, were important for the achievement of the objectives of the present work, and in the development of this study. Giving execution to that settled down by the graduation regulation in the National University of Loja. And results obtained by the application of the surveys and interview. " The companies object of studies are devoted to commercialization of products of first necessity. " Presently investigation work thinks about 5 proposals that they are: - I design Organizational and Office worker for supermarkets and self-service administered by women. - To make a plan of publicity. - Training plan for the personnel of supermarkets and self-service. - To elaborate a credit plan for the clients. - To carry out acting evaluations periodically. " The feminine administration of the self-service and supermarkets of the city of Loja, it has been beneficial in all their aspects. " The Self-service and supermarkets don't have a good organizational and administrative design. " The schedule in which bigger demand exists on the part of users to the self-service and supermarkets is to the half-day. " The employees of self-service and supermarkets consider that the feminine administration is excellent. " About the training the employees manifested that it is scarce.